Fourier Transform Infra-Red (FTIR) Spectrum Characterization of Bacillus mycoides - Trisnawati, Luh Putu Adi; Aini, Luqman Qurata; Abadi, Abdul Latief; Prillianti, Kestrillia Rega; Prabowo, Matheus Randy (Research Journal of Life Science, 2022)
The presence of Bacillus mycoides and its ability to grow and spread quickly certainly affect the growth of the target pathogen and it can cause invalid detection results. Therefore, the presence of contaminant bacteria needs to be detected to ensure the specificity of the detection results against the target pathogenic bacteria. Various kinds of detection methods are commonly used, such as ELISA (enzyme-linked immunosorbent assay) and PCR (polymerase chain reaction) are time-consuming and not always very specific. Fourier-transform infrared (FTIR) spectroscopy methods were adopted to provide a comprehensive and reliable method for bacterial analysis. In this study, FTIR spectroscopy was used as an initial guess for the identification of bacterial isolates. Our results showed that there are dominant peaks from the FTIR spectrum obtained that were most associated with protein and carbohydrate in the range of wave number 400-4000 cm-1.